A case report of severe pneumonia caused by Aeromonas dhakensis infection complicated with severe atrial septal defect - Sha, Jun; Shao, Jie; Lu, Sheng; Zhang, Mengmeng; Gu, Cheng; Deng, Yimai; Zhang, Jianfeng; Feng, Yufeng (Frontiers in Medicine, 2024)
Aeromonas dhakensis is an increasingly recognized human pathogen in recent years and was first isolated and reported in a sample of childhood diarrhea in Bangladesh. More and more cases of Aeromonas dhakensis infection have been reported in recent years. Here we report a case of severe pneumonia caused by Aeromonas dhakensis with severe atrial septal defect. The patient, a 56-year-old male, was admitted to the hospital with severe hypoxemia and severe septic shock. Detection of the patient's bronchoalveolar lavage fluid(BALF) and peripheral blood by the metagenomic Next Generation Sequencing(mNGS) indicated Aeromonas dhakensis infection.